2017
DOI: 10.1016/j.chemosphere.2017.04.104
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses of peanut roots exposed to realistic groundwater doses of arsenate: Identification of glutathione S-transferase as a suitable biomarker for metalloid toxicity

Abstract: Arsenic (As)-polluted groundwater constitutes a serious problem for peanut plants, as roots can accumulate the metalloid in their edible parts. Characterization of stress responses to As may help to detect potential risks and identify mechanisms of tolerance, being the induction of oxidative stress a key feature. Fifteen-day old peanut plants were treated with arsenate in order to characterize the oxidative stress indexes and antioxidant response of the legume under realistic groundwater doses of the metalloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 93 publications
(90 reference statements)
2
19
0
Order By: Relevance
“…Different letters indicate significant differences between A. brasilense strains for the same As V dose. Different numbers indicate significant differences between As V doses for each inoculated strain (P < 0.05) according to a symbiotic interaction like soybean and peanut exposed to As or Cd (Bianucci et al, 2017(Bianucci et al, , 2018(Bianucci et al, , 2019Bianucci, Fabra, & Castro, 2012;Bianucci, Sobrino-Plata, et al, 2012). In this regard, previous work showed that maize inoculation with CD restrained arsenic translocation to aerial parts, limiting grain contamination when compared to Az39 (Peralta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different letters indicate significant differences between A. brasilense strains for the same As V dose. Different numbers indicate significant differences between As V doses for each inoculated strain (P < 0.05) according to a symbiotic interaction like soybean and peanut exposed to As or Cd (Bianucci et al, 2017(Bianucci et al, , 2018(Bianucci et al, , 2019Bianucci, Fabra, & Castro, 2012;Bianucci, Sobrino-Plata, et al, 2012). In this regard, previous work showed that maize inoculation with CD restrained arsenic translocation to aerial parts, limiting grain contamination when compared to Az39 (Peralta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The root samples were ground in liquid nitrogen and the powder obtained was homogenized according to the enzyme evaluated. The supernatant from the homogenates for SOD (EC 1.15.1.1), CAT (EC 1.11.1.6), GPX/PRX (EC 1.11.1.9), GR (EC 1.6.4.2), and GST (EC 2.5.1.18) were obtained according to the methodology detailed by Bianucci et al (2017), and for MDHAR (EC 1.6.5.4) and DHAR (EC 1.8.5.1) as reported by Peco et al (2020). Protein concentration in plant extracts was determined according to Bradford (1976), using bovine serum albumin as standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione S‐transferase belongs to the family of phase II detoxification enzymes with a predominant peroxidase activity (Townsend & Tew, ; Vontas, Small, & Hemingway, ). This enzyme depleted glutathione directly to detoxify organic peroxides, radicals and xenobiotics and thus regulating cells tolerance and promoting oxidising conditions (Anjum et al, ; Bianucci et al, ; Schröder, Lyubenova, & Huber, ). It was reported that cytochrome P450 monooxygenase, glutathione S‐transferase, and AKR, were all pivotal in detoxification of aflatoxin B (Hayes, Judah, & Neal, ; Knight, Primiano, Groopman, Kensler, & Sutter, ).…”
Section: Discussionmentioning
confidence: 99%
“…GSTs are enzymes that are capable of catalyzing xenobiotic complexation with GSH, making the pollutant less reactive in the intracellular environment. High GST activity can be considered to be a biomarker of As tolerance in plants (Bianucci et al 2017). Although submerged leaves have experienced increases in GST activity, the arsenic amount in their tissues may have generated a stress that exceeded their tolerance ability.…”
Section: Adinan Alves Da Silva Juraci Alves De Oliveira Fernanda VImentioning
confidence: 99%